Meningkatkan Omzet Penjualan Keripik Tempe “Wicontris” dengan Pemanfaatan Media Sosial sebagai Sarana Promosi di Desa Widorokandang Kecamatan Sidorejo Kabupaten Magetan - Ervina Duwi Utari; Maulida Nurhidayati (Institut Agama Islam Negeri Ponorogo, 2023)
Micro-Small and Medium Enterprises (MSMEs) are enterprises carried out by individual groups or a business body that are currently very influential on the economy. The existence of MSMEs in Magetan Regency has an important role in advancing the local economic sector with various enterprises of agricultural output of the Magetan community that need to gain more appreciation and support to be able to develop this enterprise, but of course it also has problems or barriers between them related to marketing strategy, interest in entrepreneurship, and packaging of products that are less attractive. Then, if seen from the problem in this case, the solution offered is socialization regarding the recognition of the use of social media as a means of product promotion and also giving motivation to grow the interest of entrepreneurs with the improvement of marketing strategies such as logos or labels that will be given on each product packaging as well as an explanation about better management in business management. The result of this activity is that MSMEs actors understand the materials submitted, namely about marketing strategies and innovation on products and branding on social media or marketplaces.